Pengembangan Media Big Book Untuk Meningkatkan Kemampuan Literasi Anak Usia 5-6 Tahun - Gunanti Setiyaningsih; Amir Syamsudin (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2019)
This study aimed to develop a big book media based on fieldwork, needs analysis, and the study of literature in kindergarten. This research and development is adopting the model of Borg & Gall with the stages consisting of: (1) research and information collecting, (2) planning, (3) developing the preliminary form, (4) preliminary filed testing, (5) main product revision, (6) main filed testing, (7) operational product revision, (8) operational field testing, and (9) final product revision. The subjects of the preliminary field test was one class, and those for field test were five classes. The subjects of the operational testing were eleven classes. The data was collected through interviews, validation product, observation, and questionnaires. The data analysis technique used was inter-rater reliability and Cohen’s Kappa with SPSS program version 22. The result of the research was the big book media and its guide book that consisted of introduction, basic competencies and indicators, steps of using the media, and daily activity plan. The result of material expert showed that the material was in a sufficient category. The result of media expert showed that the media was excellent. The result of preliminary field test, field test, and operational test were valid according to Aiken validity. The agreement of teachers in field test with Kappa coefficient value showed 50% or moderate. The agreement of teachers in operational test with Kappa coefficient value showed 51,78% or moderate. The literacy ability of children at operational test improved well.